Politics of legal reform - López-de-Silanes, Florencio (UN New YorkUS, 2002)
Identifies the forces for and against legal reform and reviews the role these forces play in episodes of reform. Seeks to determine what constitutes good laws and regulatory mechanisms, as well as how to make them enforceable in different countries.